2016
DOI: 10.1371/journal.pone.0154571
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Mycobacterium tuberculosis Complex Genetic Diversity Profiles in Tanzania and Other African Countries

Abstract: The aim of this study was to assess and characterize Mycobacterium tuberculosis complex (MTBC) genotypic diversity in Tanzania, as well as in neighbouring East and other several African countries. We used spoligotyping to identify a total of 293 M. tuberculosis clinical isolates (one isolate per patient) collected in the Bunda, Dar es Salaam, Ngorongoro and Serengeti areas in Tanzania. The results were compared with results in the SITVIT2 international database of the Pasteur Institute of Guadeloupe. Genotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 64 publications
10
31
0
1
Order By: Relevance
“…These findings are in accordance with most recent studies from the other African countries reporting a predominance of M. tuberculosis strains ( 25 28 ). The high prevalence of M. tuberculosis detected in our investigation suggests that this predominance of M. tuberculosis strains might equally be the case for Congo, mainly driven by the newly described Congo-type sublineage.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in accordance with most recent studies from the other African countries reporting a predominance of M. tuberculosis strains ( 25 28 ). The high prevalence of M. tuberculosis detected in our investigation suggests that this predominance of M. tuberculosis strains might equally be the case for Congo, mainly driven by the newly described Congo-type sublineage.…”
Section: Discussionsupporting
confidence: 93%
“…We found that, the Central Asian strains (CAS) genotype (lineage 3) were the predominant lineages (Table 5), with no evidence of any change in terms of the CAS dominance over the past few years in Tanzania [50]. The CAS is among the prevalent lineage in the Indian subcontinent, South-East Asia, the Middle-East and East-Africa [51], showing a North-South divide along the Tropic of Cancer in the Eastern hemispheremainly in Asia, and partly prolonged along the horn of Africa [51,52]. The dominance of CAS lineages in our local settings might be attributed to early contact due to migration and trade between people in Asian and East Africa countries.…”
Section: Discussionmentioning
confidence: 99%
“…This illustrates the ability of “modern” lineages to thrive in co-existence with the pre-existing “ancient” (TbD1+) lineages such as Lineage 1 in our case, perhaps because of the comparably higher virulence [16,37]. The neighboring countries of Tanzania on the other hand show comparable M. tuberculosis lineage composition [38,39], indicating common demographic histories and ongoing exchanges that resulted into distinct M. tuberculosis populations. The frequency of Lineage 2–Beijing in Tanzania, like in most parts of the continent except for South Africa [38,39] is relatively low, despite the long-standing African- Asian contacts [39].…”
Section: Discussionmentioning
confidence: 70%
“…The neighboring countries of Tanzania on the other hand show comparable M. tuberculosis lineage composition [38,39], indicating common demographic histories and ongoing exchanges that resulted into distinct M. tuberculosis populations. The frequency of Lineage 2–Beijing in Tanzania, like in most parts of the continent except for South Africa [38,39] is relatively low, despite the long-standing African- Asian contacts [39]. Evidence from recent studies show that Lineage 2-Beijing was only recently introduced into Africa [15,40].…”
Section: Discussionmentioning
confidence: 99%